2020
DOI: 10.1097/gme.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

Can walking exercise programs improve health for women in menopause transition and postmenopausal? Findings from a scoping review

Abstract: Objective: Our goal was to explore the range and characteristics of published papers on therapeutic walking programs for menopausal women and to identify program features that resulted in successful outcomes including reduced symptoms and improved long-term wellness. Methods: We searched biomedical and exercise-related databases for articles published up to June 1, 2017, using keywords related to menopause and walking. Data were collected into EndNote X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…It can also be concluded from participants' feedback that walking is beneficial for their physical health promotion and that most walking programs have health benefits for women. A scoping review reported that an average weekly walking length of 162 minutes was suggested, which complied with health guidelines recommended by North American authorities 35 . It has also been shown that relaxation techniques benefit in relieving perimenopausal symptoms 26 .…”
Section: Discussionmentioning
confidence: 83%
“…It can also be concluded from participants' feedback that walking is beneficial for their physical health promotion and that most walking programs have health benefits for women. A scoping review reported that an average weekly walking length of 162 minutes was suggested, which complied with health guidelines recommended by North American authorities 35 . It has also been shown that relaxation techniques benefit in relieving perimenopausal symptoms 26 .…”
Section: Discussionmentioning
confidence: 83%
“…Exercise improves cardiorespiratory capacity, weight preservation/loss (with diet), bone mineral density, and muscle strength in postmenopausal females. 20 Furthermore, walking programs improve cardiovascular markers, lipid and carbohydrate metabolism disorders (thereby decreasing hypertension), 20 , 21 physical and mental health, and sexual quality of life. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing exercise to no exercise or to wait groups showed no improvement of VMS with walking. Two studies comparing walking exercise to MHT demonstrated superior efficacy of MHT [79]. NAMS and other regional menopause societies concluded that although there are many health benefits for women from exercise, randomized control trials do not support it as an intervention for VMS [34,80].…”
Section: Exercisementioning
confidence: 99%